Monitoring zone-associated implantable cardioverter defibrillator shock: A case report - Hisayasu Matsuzaki; Yukiko Nakano, MD; Shigeyuki Okahara; Satoshi Miyamoto; Hidenobu Takahashi; Katsuhiko Imai, MD; Taijirou Sueda, MD; Yasuki Kihara, MD (Journal of Arrhythmia, 2012)
A 41-year-old man with Brugada syndrome, who had been implanted with an ATLAS+DR V-243 (St. Jude Medical, Inc., St. Paul, MN, USA) dual-chamber implantable cardioverter defibrillator (ICD) for secondary prevention of arrhythmia, received an inappropriate shock. The ventricular fibrillation (VF) zone was programmed to deliver maximum output shock therapy at a detection threshold of greater than 214 beats per min, and 12 consecutive instances of crossing the threshold constituted 1 VF. The monitoring zone was programmed to detect heart rates of greater than 160 beats per min with all supraventricular tachycardia (SVT) discriminators in the “ON” mode, and 12 consecutive instances of the heart rate exceeding 160 beats per min constituted 1 SVT. The ICD shock was delivered after an episode of sinus tachycardia that continued for 3 min 15 s. The monitoring zone is effective for detecting asymptomatic ventricular tachycardia or SVT, and therapy is not usually set up in this zone. Here, we report the possibility that in some patients implanted with certain types of ICD devices, the monitoring zone may become a factor in the delivery of an inappropriate shock.